REMINDER TIME APPLICATIONS ON PC USING MICROSOFT VISUAL BASIC 6.0 - Fritz Manugi Napitupulu Maradona; Yulina. S. Kom., MMSI Yulina. S. Kom., MMSI (Jurnal Sistem Informasi, 2006)
With the progress of the development of increasingly sophisticated informationtechnology, computers play an important role therein. Moreover computer equippedwith facilities and infrastructure are developed at this time due to make users forget touse a computer in a long time without both optimize the time to do another job.Alarm is a media alert while taking a break can be useful in reminding. The alarm onthe PC because it is expected to help computer users on inflammation in remindingthe things important to optimize the answer in time.